A H-aggregating fluorescent probe for recognizing both mercury and copper ions based on a dicarboxyl-pyridyl bifunctionalized difluoroboron dipyrromethene - Xie, Hao-Ran; Gu, Ya-Qi; Liu, Li; Dai, Jing-Cao (New journal of chemistry, 2020)
An interesting dicarboxyl-pyridyl functionalized difluoroboron dipyrromethene dye probe (2,6-diCO 2 H-BODIPY), showing molecular packing in a 3D microporous supramolecular framework with 1D channels, is successfully fabricated and characterized, exhibiting a remarkable dual-responsive fluorescence sensitivity for recognizing both Hg 2+ and Cu 2+ ions based on the ion-induced H-aggregation. A difluoroboron dipyrromethene fluorescent probe is fabricated for recognizing both Hg 2+ and Cu 2+ ions based on an extraordinary ion-induced H-aggregation.